ANALISIS POLA SEWA LAHAN (LAND RENT) PADA USAHATANI BAWANG MERAH DI KABUPATEN SUMBAWA - efendy, Efendy; FR, Aeko Fria Utama (JURNAL AGRIMANSION, 2023)
This research aims to: (1) determine more efficient land rental patterns; (2) knowing the costs and income of farmers in each shallot farming pattern in the rental system; (3) determine the level of efficiency of farmer input use in shallot farming in the land rental system in Sumbawa Regency. Research using descriptive methods, qualitative and quantitative data types. Determination of villages was carried out using a purposive sampling method, namely Plampang District. Respondents were determined using proportional random sampling with 30 farmer respondents. The research results show that there are two patterns, namely Pattern 1 and Pattern 2, where Pattern 1: one year before planting, while Pattern 2: one year, half before planting and half before harvest. The average land rental price for MT II shallot farming in Pattern 1 is IDR 6,395,348.84/Ha, while the average land rental price in Pattern 2 is IDR 6,524,822.69/Ha before discounts and IDR 6,285,106 .38/Ha after discount. (2) The average cost of shallot production in Plampang District, Sumbawa Regency at MT II in Pattern 1 is IDR 45,421,988.91/Ha/MT, while in Pattern 2 it is IDR 35,282,003.13/Ha/MT. Meanwhile, the average income in Pattern 1 is IDR 27,462,774.04/Ha/MT, while in Pattern 2 it is IDR 21,741,188.33/Ha/MT. (3) The ratio of Marginal Product Value (NPMx) to the Average Price of Production Factors (Px) for each variable does not have a value equal to one. The use of production factors of land area (X1), seeds (X2), and labor (X3) is not efficient. Meanwhile, the use of fertilizer (X4), pesticides (X5), and land rental (X6) is inefficient.